ANALISIS KADAR AIR, KADAR PROTEIN DAN KADAR KALIUM TEPUNG BIJI NANGKA (Artocarpus heterophyllus) - Apriliana Ballo; Sonya Titin Nge; Andriani Rafael; Novi Ivoni Bullu (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Jackfruit seed is usually thrown away after being consumed as fresh fruit or being processed as a jackfruit crackers and other food product. Jackfruit seed consist of carbohydrate (36,7 g/100 g) and also as a source minerals. The availability of jackfruit seed was found abundance but the use of it not maximize yet. The flour from jackfruit seed can be used an alternative for making food product. The flour extracted from (40,891) jackfruit seed have longer storage time and easy to turn it to other product. The aim of this research was to measure water content, protein content and potassium level from jackfruit flour. The method used during the research was experimental research which is to compare the treatment between boiled and fresh jackfruit seed. The findings showed that water content of boiled jackfruit seed are higher (43,844 unit) than the flour of the fresh jackfruit flour (40,891 unit).The protein content are lowest of flour of boiled jackfruit seed with the value of 7,51 and highest of fresh jackfruit seed with value of 7,72. The potassium content the flour of boiled jackfruit seed was higher with the value of 0.062 than the flour of fresh jackfruit seed with value of 0.006. Kata kunci: Biji Nangka, Kadar Air, Kadar Kalium, Kadar Protein, Tepung Biji Nangka.